A Borophagine canid (Carnivora: Canidae: Borophaginae) from the middle Miocene Chesapeake Group of eastern North America. (9th May 2016) - Jasinski, Steven E.; Wallace, Steven C.
Abstract: A tooth recovered from the middle Miocene Choptank Formation (Chesapeake Group) of Maryland is identified as a new cynarctin borophagine (Canidae: Borophaginae: Cynarctina), here called Cynarctus wangi n. sp. The tooth, identified as a right upper second molar, represents the first carnivoran material reported from the Choptank Formation and part of a limited record of borophagine canids from eastern North America. As ? Cynarctus marylandica (Berry, 1938), another cynarctin borophagine from the older Calvert Formation, is known only from lower dentition, its generic affinities are uncertain. However, features of this new material are compared to features of ? C . marylandica through occlusal relationships, allowing for referral to a distinct species. Even so, the Choptank Formation material still offers two possible scenarios regarding its identification. In one, its geographic and stratigraphic provenance could imply that it belongs to ? C . marylandica . If this were correct, then the generic placement of ? C . marylandica would be correct and the taxon would be more derived than some other Cynarctus species in regard to hypocarnivory, and less derived than others. The second possibility, and the one believed to be most probable, is that a distinct cynarctin borophagine is present in the Chesapeake Group in strata younger than the type specimen of ? C . marylandica . This new borophagine canid expands the sparse fossil record of this group in northeastern North America and furthers our knowledge of the fossil record of terrestrial taxa in this region.